Women Living With HIV in the South: Facilitators and Barriers to HIV Care - Caskey, Justine Nakanishi (East Carolina University, 2023)
Currently, the Southern states in the United States (US) are facing an epidemic of HIV that disproportionately affects the region more than any other region of the country. The percentage of new diagnoses in southern rural communities remains steady but women living with HIV (WLWH) are facing worse health outcomes compared to men living with HIV. The purpose of this project was to determine the facilitators and barriers to HIV care engagement and antiretroviral (ART) medication adherence for women living with HIV who reside in rural areas of the Southeast region of the US. This qualitative descriptive study utilized secondary data collected in my project mentor’s parent study titled “Modeling perceptions of social location and decision-making to develop targeted messaging promoting HIV care engagement and ART adherence among women living with HIV in the South” [NIH/NINR: 1R21NR020164]. The parent study included 40 in-depth interviews using a semi-structured interview guide with WLWH from the Southeast region of the US to understand the facilitators and barriers they experience with engaging in HIV care and adhering to ART medications. Ten (N=10) of the 40 women interviewed, the sample for this project, reported residing in a rural area based on their zip code of residence and the US Census designations for urbanized locations. First-level in vivo coding and second-level pattern coding was conducted. Analytic lines for further thematic analysis of the entire data set were then identified in collaboration with my project mentor and organized under the overarching categories of either facilitators or barriers to HIV Care engagement and medication adherence. For WLWH in rural areas, the themes identified as facilitators were Accessibility to Care: Personal Resources and Structural Facilitators. The themes identified as barriers were Lack of Accessibility to Care Due to Proximity, Lack of Accessibility to Care: Personal Resources, Structural Barriers, Lack of Social Support, and Issues of Anonymity. These findings differed from the findings in a review of the literature. The literature identified the main rural facilitators as social support and telemedicine and the main rural barriers as HIV-related stigma and confidentiality concerns. Therefore, additional research is needed to investigate the specific experiences of women living with HIV in the South to shed light on different strategies that may enhance their engagement in HIV care and adherence to ART medications.
Keywords: HIV Care Engagement and Antiretroviral Medication Adherence; Facilitators and Barriers; Rural